A method for evaluating business models implementation process. Issue 4 (4th July 2016) - Batocchio, Antonio; Ghezzi, Antonio; Rangone, Andrea
Abstract : Purpose: – The purpose of this paper is to identify and discuss the reasons why business models fail, while also identifying the features necessary to develop a method that enables the evaluation of the implementation process of the business model, and is able to help in its development. Design/methodology/approach: – The proposed method (roadmap for implementation of business models – RIBM) is composed of nine steps, and seven initials conditions (limitations). Such conditions reduce its complexity (e.g. performance management system is defined in the company). Findings: – Some reasons why business models fail (alignment between value proposition and customer segment (value proposition); business model financial viability (costs and revenue); environmental constraints not fully integrated with the design of the business model (environment); business model execution (management), etc.) and made some considerations about the implementation of business models. Research limitations/implications: – This work was developed in a small business (with a small team and the external member). The business complexity level and number of processes involved are much smaller when compared with a mid-size or large company. Another factor that contributed to mitigating the problem is that the enterprise had a well-structured report once the owners had made annual analysis and discussed how to improve and expand the business. Practical implications: – In this application, RIBM showed a potential tool to minimize flaws in implementation processes of business models. Originality/value: – The business model concept is relatively new in the literature. And because of its strategic importance has been the target of all major schools in the area. This work, in particular, deals with the question-related failures that occur in the process of implementing business models.